Drawing for the Project: Dimension and Space for an Architecture Imagined before its Realization (diségno, 2023)
The languages with which we communicate thoughts, sensations and ideas are attempts to make the feelings we experience legible and above all aim at the desire to share our perspectives on life with the people around us. We learn as children to attempt a description of the things we feel on an emotional level, in a synthesis that respects rules of syntax and grammar, primarily in the language that belongs to us, because in this way we try to make things transmissible that do not seem to be so and which concern an internal sphere which, apparently, does not have such a clear form of communication and is instead more soul and chemistry than sound and vision. [read more]